SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU PADA SMP NEGERI 1 NDONA KABUPATEN ENDE NUSA TENGGARA TIMUR - Rando, Agnes Remi; Rawe, Aschari Senjahari (STIT Pringsewu, 2019)
AbstractionThis study aims to reveal the academic supervision program in increasing teacher professionalism conducted by the Ndona 1 Public Middle School. The approach used is qualitative with descriptive methods and data collection techniques used are interviews, observation, documentation. The results of the study show that the academic supervision carried out by School failure has a very good impact in order to increase the professionalism of teachers. From the available data, it shows that the role of principals in increasing teacher professionalism is very good by carrying out supporting activities by sending teachers to participate in various trainings, holding information and technology training , involving teachers in the subject teacher discussion activities.